An analytical inquiry into Islamic and Western methodologies of studying world religions. - Yousif, Ahmad (Praeger, 2009)
As in the early Islamic period, so today Muslims scholars and students face several challenges in their study of world religions. Some of these challenges are common to Muslim and Western scholarship on the subject, while others are peculiar to Muslim scholarship. They range from the challenge of defining and delimiting the field to those associated with methodology. This paper examines some of these challenges, drawing upon the classical Islamic heritage, the experience of Western comparativists, and the works of modern Muslim scholars in the field. First, however, it will deal with the question, Why do Muslim scholars need to make a serious study of other major world religions? To be sure, some Muslims are opposed to such an exercise, arguing that it will do more harm than good. It is, therefore, necessary to ask what led Muslim scholars, especially in the past, to study other religions.